RESEARCH ON THE DESIGN METHOD OF THE AEROSPACE STANDARD THIN-WALLED SPECIMEN TO MEASURE THE PRECISION OF MACHINE TOOL - JIANG XiaoHui; ZHANG ZhenYa; LI HaoLin; YAO Yao (Jixie qiangdu)
The design and optimization of standard parts to the machine tool is always being the focus of domestic and foreign countries,which is helping for the machine tool inspection and assessment of the performance. In this study,according to the advantages and disadvantages of standard specimen of the universal five-axis NC machine tools,comparing the structural characteristics and machine features for the testing performance of ISO international standard specimen, NASA979 series specimen,"S"shape of the specimen and other specimens. The most characteristics of modern aviation parts are combined to design the "X"form of new aircraft thin-wall standard specimen. By analyzing the "X"shaped aviation thin-walled specimen with the finite element method,the open,close angles and curvature continuity curves are calculated and discussed. Based on the results of finite element analysis,it’s the first time to put forward the processing complexity coefficient concept,compares the cutting force and thermal load,the cutting force dominates in the residual stress generated,this paper only consider the effect of cutting force,to evaluate the characteristics of the"X"shape aviation thin-wall specimen in the geometric model and mechanical structure design in-depth. It proved that "X"shaped aviation thin-wall specimen is better than the other standard specimens in comprehensively reflecting the multi-axis linkage and dynamic stiffness characteristics of the CNC machine possess,showing more comprehensive and superiority in the aspect of detection. All above conclusions provide the scientific basis and effective approach for integrated precision detection characteristic of five-axis CNC machine based on the "X "shaped new aircraft thin-walled standard specimen.